Fully metallic copper 3D-printed electrodes via sintering for electrocatalytic biosensing. (December 2021) - Redondo, Edurne; Pumera, Martin
Abstract: 3D printing is a very useful manufacturing method for the fabrication of electrochemical devices. Typically, accessible fused filament fabrication (FFF) is the most used method; but it is limited to the materials of use, mainly to carbon/polylactic acid blend. The use of metal 3D printed devices produced by FFF would offer very useful combination of advantages such as robustness, and electrocatalytic surfaces at a low cost. Here, 3D printed copper electrodes were successfully prepared by FFF followed by a sintering step. The physical and electrochemical properties of FFF 3D printed copper electrodes were characterised using various complementary techniques, while the electrochemical performance was evaluated for the non-enzymatic sensing of glucose as a first demonstration of applicability. Such low-cost 3D-printing method for fabrication of metallic electrodes will be further applicable for a wide variety of devices. Highlights: 3D printed copper electrodes were prepared Sintering temperature has been optimized for the best electrochemistry Capability of 3D printed copper electrodes as sensor was shown Abstract : Image, graphical abstract .